Monoclonal antibodies targeting two immunodominant epitopes on the Spike protein neutralize emerging SARS-CoV-2 variants of concern - Kovacech, Branislav; Fialova, Lubica; Filipcik, Peter; Skrabana, Rostislav; Zilkova, Monika; Paulenka-Ivanovova, Natalia; Kovac, Andrej; Palova, Denisa; Rolkova, Gabriela Paulikova; Tomkova, Katarina; Csokova, Natalia Turic; Markova, Karina; et al. (EBioMedicine, 2022)
BACKGROUND: The emergence of new SARS-CoV-2 variants of concern B.1.1.7 (Alpha), B.1.351 (Beta), P.1 (Gamma) and B.1.617.2 (Delta) that harbor mutations in the viral S protein raised concern about activity of current vaccines and therapeutic antibodies. Independent studies have shown that mutant variants are partially or completely resistant against some of the therapeutic antibodies authorized for emergency use. METHODS: We employed hybridoma technology, ELISA-based and cell-based S-ACE2 interaction assays combined with authentic virus neutralization assays to develop second-generation antibodies, which were specifically selected for their ability to neutralize the new variants of SARS-CoV-2. FINDINGS: AX290 and AX677, two monoclonal antibodies with non-overlapping epitopes, exhibit subnanomolar or nanomolar affinities to the receptor binding domain of the viral Spike protein carrying amino acid substitutions N501Y, N439K, E484K, K417N, and a combination N501Y/E484K/K417N found in the circulating virus variants. The antibodies showed excellent neutralization of an authentic SARS-CoV-2 virus representing strains circulating in Europe in spring 2020 and also the variants of concern B.1.1.7 (Alpha), B.1.351 (Beta) and B.1.617.2 (Delta). In addition, AX677 is able to bind Omicron Spike protein just like the wild type Spike. The combination of the two antibodies prevented the appearance of escape mutations of the authentic SARS-CoV-2 virus. Prophylactic administration of AX290 and AX677, either individually or in combination, effectively reduced viral burden and inflammation in the lungs, and prevented disease in a mouse model of SARS-CoV-2 infection. INTERPRETATION: The virus-neutralizing properties were fully reproduced in chimeric mouse-human versions of the antibodies, which may represent a promising tool for COVID-19 therapy. FUNDING: The study was funded by AXON Neuroscience SE and AXON COVIDAX a.s.
Keywords: Antigenic Drift and Shift; Immunodominant Epitopes; angiotensin-konvertující enzym 2; Humans; Antineoplastic Agents, Immunological; Variants of concern; antigenní drift a shift; Protein Binding; Neutralization Tests; imunodominantní epitopy; Antibodies, Monoclonal; mutace; Lung; lidé; zvířata; Angiotensin-Converting Enzyme 2; myši; plíce; Mice; COVID-19; Kinetics; Neutralizing antibodies; glykoprotein S, koronavirus; vazba proteinů; farmakoterapie COVID-19; monoklonální protilátky; Spike Glycoprotein, Coronavirus; protinádorové látky imunologicky aktivní; Escape mutation; Animals; Mutation; neutralizační testy; SARS-CoV-2; Disease Models, Animal; COVID-19 Drug Treatment; kinetika; modely nemocí na zvířatech